MADDATE, SUFISM, AND MORAL EDUCATION: A STUDY ON TAREKAT KHALWATIYAH SAMMAN IN BULUMPAREE, BONE, SOUTH SULAWESI - Sumiati; Ridhwan; Amir; Khaeruddin Kiramang (Master Program of Sociology, Universitas Malikussaleh,, 2025)
This study aims to discuss Sufism education within the zikir ritual (Maddate) of Khalwatiyah Samman in Bulumparee Village, elaborating on the implementation process and identifying the values contained therein. This research is a qualitative field study, examining and investigating respondent sources found directly in the field through observation, interviews, and documentation. The results of this study indicate that: First, Tarekat Khalwatiyah Samman entered Bone Regency brought by a Bugis Bone nobleman named Abdullah Munir in the 19th century. Second, the implementation of zikir jahr of Tarekat Khalwatiyah Samman is performed after Isya and Subuh prayers, utilizing the phrases Lailahaillallah, Allah-Allah, Huwa-Huwa, Ah-Ah. Before performing zikir jahr, several things need to be prepared, namely reciting salawat for the Prophet Muhammad, the Prophet's Companions, and the Mursyids of Khalwatiyah Samman, reciting Surah Al-Fatihah, and then sitting in a circle. Zikir Khalwatiyah Samman aims to draw closer to Allah swt., eliminate despicable behaviors, and strengthen a servant's faith in the Creator. Zikir is beneficial for making one's heart calm, serene, and peaceful. Third, Zikir is not only a means to draw closer to Allah swt., but also contains Sufism values within it, such as the values of al taubat, al zuhud, wara, mahabbah, takwa, tawakkal, adab, sabar, ikhlas, warid, and muraqabah. Thus, sociologically, through maddate or zikir, it is able to provide moral education for the community of Bulumparee Village to be peaceful and mutually respectful, and able to strengthen social cohesion and solidarity.